The design of information technology strategic plans in educational institutions - Astuti, Dwi; Winarno, Wing Wahyu; Sofyan, Amir Fatah (Research and Social Study Institute (ReSSI), 2018)
Strategic Plan, which is usually taken from Vision, Mission, Objectives, Policies, Programs and activities that are oriented towards the goal for a certain period relating to the main tasks and functions of the Agency / Institution, prepared by consider the developments of strategic environment, the sustainability of organization without strategic plan will not be directed and guaranteed because there are no management guidelines and system improvements in order to increase the competition with other business actors. STMIK Bina Patria is a private university (PTS), but it does not have an information system (SI) strategic plan. The information system contributes to improve the quality of students’ services, operational efficiency, and students’ satisfaction. With SI / IT, the monitoring, coordination, and decision can be performed effectively. The goal can be achieved if the organization has a clear plan. And, researchers make an IT strategic plan for STMIK Bina Patria according to the TOGAF Framework with data analysis methods of Value Chain, Critical Success Factors, and SWOT. The analysis results showed that by the availability of 4 applications, 3 applications do not require any improvement, namely SI-KEU, E-LEARNING and E-JOURNAL. In contrast, an application which is SI-AKAD requires additional features. There were 5 proposed applications to be built, namely SI-PMB, SI-ALUMNI, SI-MUTU, SI-PERPUST and SI-DASHBOARD. All of application proposals are mapped into the application development roadmap within the next 5 years.